2021
DOI: 10.1128/mbio.01966-21
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Antibiotics Exist?

Abstract: In the struggle with antibiotic resistance, we are losing. There is now a serious threat of moving into a postantibiotic world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 106 publications
(123 reference statements)
0
28
0
Order By: Relevance
“…The present study revealed that the physiological concentration of diaphorin, a polyketide synthesized by an obligate symbiont of psyllids, inhibits the growth of B. subtilis (Gram-positive bacteria) but promotes the growth of E. coli (Gram-negative bacteria). As exemplified by some antibiotics, certain secondary metabolites have inhibitory effects only on Gram-positive bacteria that lack the outer membrane, an effective barrier that protects Gram-negative bacteria from toxic compounds (2, 4). However, it is unique that a single molecule clearly exhibits opposite effects on distinct bacterial lineages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study revealed that the physiological concentration of diaphorin, a polyketide synthesized by an obligate symbiont of psyllids, inhibits the growth of B. subtilis (Gram-positive bacteria) but promotes the growth of E. coli (Gram-negative bacteria). As exemplified by some antibiotics, certain secondary metabolites have inhibitory effects only on Gram-positive bacteria that lack the outer membrane, an effective barrier that protects Gram-negative bacteria from toxic compounds (2, 4). However, it is unique that a single molecule clearly exhibits opposite effects on distinct bacterial lineages.…”
Section: Discussionmentioning
confidence: 99%
“…subtilis (Gram-positive bacteria) but promotes the growth of E. coli (Gram-negative bacteria). As exemplified by some antibiotics, certain secondary metabolites have inhibitory effects only on Gram-positive bacteria that lack the outer membrane, an effective barrier that protects Gram-negative bacteria from toxic compounds (2,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our modelling tools and understanding of biology have improved since Bonhoeffer’s publication. The significant impact of phenomena such as bystander selection [ 61 ] are better understood, and there has been a more recent push toward integrating both within host and between host models [ 62 ]. Similarly, in the area of clinical policy, diagnostic-informed strategies such as the ‘search and destroy’ ABR policy implemented in the Netherlands [ 48 , 49 , 60 ] have been mentioned only briefly in this article.…”
Section: Discussionmentioning
confidence: 99%
“…Alexander Fleming discovered Penicillin (P) in 1928 when noticed that the fungus Penicillium notatum inhibited the growth of Staphylococcus. Gerhard Domagk, in 1935, demonstrated that Prontosil (the first sulphonamide drug) was effective against Streptococcus infections and puerperal fever [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%